Galvanizing Culture for Nigeria's Development - Ngozi Ezenagu (ABUAD Journal of the Humanities-AGIDIGBO)
Culture is an all embracing concept which constitute in its entirety 'the way of life' of a group of people. This involves morals, values, norms, among others, which influence man's perception and invariably affect how he relates with his environment for development. Hitherto, development itself is multifaceted. Therefore, this paper posits that it is only a culture based development that can address the needs of its populace. Any meaningful development must be rooted in the cultural values of the nation in order to retain its identity. Most developing nations like Nigeria are compromising their national identity for the price of development. A retrospect of Nigeria pre-colonial days gave an overview of culture oriented development. The paper conclusively, launched the need for Nigeria to imbibe development compatible to its culture.